Adjuvant radiotherapy with brachytherapy boost in soft tissue sarcomas - Cortesi, Annalisa; Galuppi, Andrea; Frakulli, Rezarta; Arcelli, Alessandra; Romani, Fabrizio; Mattiucci, Gian Carlo; Bianchi, Giuseppe; Ferrari, Stefano; Ferraro, Andrea; Farioli, Andrea; Gambarotti, Marco; Righi, Alberto; et al. (Journal of Contemporary Brachytherapy, 2017)
Purpose: The standard primary treatment for soft tissue sarcoma (STS) is a wide surgical resection, preceded or followed by radiotherapy. Purpose of this retrospective study was to assess the efficacy of perioperative brachytherapy (BRT) plus postoperative external beam radiation therapy (EBRT) in patients with intermediate-high risk STS. Material and methods : BRT delivered dose was 20 Gy. External beam radiation therapy was delivered with 3D-technique using multiple beams. The prescribed dose was 46 Gy to the PTV. Neoadjuvant and adjuvant chemotherapy (CHT) was used in patients with potentially chemosensitive histological subtypes. The primary aim of the study was to analyze overall survival (OS) and local control (LC) in a large patient population treated with surgery, perioperative BRT, and adjuvant EBRT ± CHT. Secondary objective was to identify prognostic factors for patients outcome in terms of LC, disease-free survival (DFS), and OS. Results : From 2000 to 2011, 107 patients presenting 2-3 grade (FNLCC) primary or recurrent STS were treated with surgery, perioperative BRT, and adjuvant EBRT ± CHT. Five-year LC and OS were 80.9% and 87.4%, respectively. At univariate analysis, a higher LC was recorded in primary vs. recurrent tumors (p = 0.015), and in lower limb tumors vs. other sites (p = 0.027). An improved DFS was recorded in patients with lower limb tumors vs. other sites (p = 0.034). Conclusions : The combination of BRT and EBRT was able to achieve satisfactory results even in a patients population with intermediate-high risk STS. Patients with recurrent or other than lower limb sited tumors show a worse LC.